Capital asset pricing model as an analysis of the efficient grouping of stock - An Suci Azzahra; Tengku Eka Susilawaty; Alyuna Andini (Institute of Computer Science (IOCS), 2023)
This research is applied research with descriptive research methods using secondary data. The purpose of this study is to find out which stocks are efficient and inefficient by using the CAPM method to avoid investment mistakes so that investors can understand the CAPM method to help them determine the best investment decisions. The population of this study is the Business-27 Index for the 2019–2021 period. The sampling method used was purposive sampling, with a total sample of 16 companies. This study uses monthly closing price data and SBI data with Business Index data 27. The results show that there are seven efficiency stocks in the CAPM model, namely ADRO, BBCA, BBNI, BBRI, BMRI, TLKM, and UNTR.